IoT enabled data protection with substitution box for lightweight ciphers - K.B. Sarmila; S.V. Manisekaran (Egyptian Informatics Journal)
Rapid growth in communication and networking demands the protection of highly sensitive data in the system. The cryptographic techniques used in various traditional devices and cloud environments are not applicable to resource-constrained devices like sensors, industrial controllers, and RFID tags. A lightweight cryptographic design is required for securing the data revolving around constrained devices. Symmetric block cipher techniques shaped using substitution-permutation network (SPN) structure use the powerful component, the substitution box, which is the only component that contributes to non-linearity. In this paper, a modified 5-bit Dynamic Airy Chaotic (DAC) substitution box is proposed, which uses tent-logistic mapping for obtaining confusion property. This chaotic behavior is incorporated with an improved and crafted logical function. The substitution box exhibits high dynamic chaotic behavior and maintains the structure, balancing the composition of good security strength and resource utilization. The chaotic behavior and security resistance are evaluated based on the standard parameters. The DAC substitution box demonstrates improved security with 66% less memory footprint on an average gate count compared with standard 4- and 5-bit competitors. The solution was able to obtain equally good resistance against differential attacks and increased resistance against linear attacks with 40% less linear probability value in comparison with its competitors. With the increased bit length of 5, it is observed that DAC exhibits excellent flexibility with traditional block cipher techniques, thus simplifying the use of such a solution as a building block of cryptographic primitives.